VISTA is an immune checkpoint molecule for human T cells - Lines, J. Louise (2014)
VISTA is a potent negative regulator of T cell function that is expressed on hematopoietic cells and leukocytes. VISTA levels are heightened within the tumor microenvironment where its blockade can enhance anti-tumor immune responses in mice. In humans, blockade of the related PD-1 pathway has shown great potential in clinical immunotherapy trials. Here we report the structure of human VISTA and examine its function in lymphocyte negative regulation in cancer. VISTA is expressed predominantly within the hematopoietic compartment with highest expression within the myeloid lineage. VISTA-Ig suppressed proliferation of T cells but not B cells, blunted production of T cell cytokines and activation markers. Our results establish VISTA as a negative checkpoint regulator that suppresses T cell activation, induces Foxp3 expression and is highly expressed within the tumor microenvironment. By analogy to PD-1 and PD-L1 blockade, VISTA blockade may offer an immunotherapeutic strategy for human cancer.